E-housing management system study case Jitra, Kedah / Nur Fathin Nabila Zainodin - Zainodin, Nur Fathin Nabila (2020)
Housing is one of the most important components of life in providing protection, safety, warmth and relaxing. The catalyst for a structure of the social economy depends on housing demand and supply, which is a major challenge for a country. Population growth and economic development has led to a growing demand for housing development in Malaysia. Besides that, the high demand of the house causes management system of housing growing a problem. Web-based systems are an approach to system development that is gaining public attention today. This is because web applications on web pages are more comprehensive. Therefore, the aim of these studies is to manage the housing system. The objectives are carried out is to develop E-residential of house pricing of Jitra district, Kedah and to publish housing system in internet for civilian access. The district of Kedah that Jitra was chosen as area in this study. In completing the objective this study will perform with several processes in build up a system web based. The web based system is an outcome of the studies.